ANALISIS DAYA DUKUNG KAWASAN PERMUKIMAN DI KOTA PADANG - rina, syafrina (JURNAL BUANA, 2025)
Settlement is one of the basic human needs in the context of increasing and equitable distribution of people's welfare. The analysis of the carrying capacity map of the settlement area utilizes a GIS (Geographical Information System) analysis tool by complicating variable data, namely calculating the carrying capacity of settlements, slope data, soil type, rainfall, land use. To obtain the data in this study, orientation and analysis were used by means of data collection by field observations, documentation, and library studies. Based on the results of data analysis using the population growth rate formula, the highest population growth rate in the city of Padang is in the Koto Tangah district with a population growth rate of 1.99% while the lowest population growth rate is in North Padang District, namely - 2.25%. Based on the calculation results, there are 3 sub-districts in Padang City where the population growth rate reaches a minus number, namely East Padang District by -0.01%, West Padang District -0.05% and North Padang District -2.25%.